The hills beyond - Keppeler, Jill (Keppeler, Jill. Unofficial Minecraft graphic novel., 2021)
While Mike and Maria visit their cozy base in the Minecraft-themed world they discovered, they decide to investigate the distant hills that they see from their windows. As they explore, Mike finds a new animal and Maria looks for a way to upgrade her armor.